2016
DOI: 10.1111/ijfs.13274
|View full text |Cite
|
Sign up to set email alerts
|

Powdered barley sprouts: composition, functionality and polyphenol digestibility

Abstract: This study was performed to evaluate the phytochemical composition, in vitro antioxidant capacity, antihyperglycaemic and anti‐inflammatory activities, and simulated gastrointestinal digestion of 7‐day‐old freeze‐dried barley sprouts (BS), one hybrid and one nonhybrid variety: ‘NS565’ (BSNS) and ‘Golozrni’ (BSG), respectively. BSNS expressed significantly higher (P ≤ 0.05) content of total phenols, chlorophyll and carotenoids. Phenolic compounds were the most dominant bioactives in both BSNS and BSG (713.25 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 34 publications
3
35
1
1
Order By: Relevance
“…The TPC of OSJ and WSSim was similar to the level reported by Alvarez-Jubete et al [16] for buckwheat sprouts (670 mg GAE/100 g) and higher than the level reported by the same authors for wheat sprouts (110 mg GAE/100 g). The range of TPC found in our samples was slightly lower than that reported by Aborus et al [17] for two barley varieties (from 479 to 713 mg/100 g).…”
Section: Content Of Total and Individual Phenolics In Fdspcontrasting
confidence: 84%
See 1 more Smart Citation
“…The TPC of OSJ and WSSim was similar to the level reported by Alvarez-Jubete et al [16] for buckwheat sprouts (670 mg GAE/100 g) and higher than the level reported by the same authors for wheat sprouts (110 mg GAE/100 g). The range of TPC found in our samples was slightly lower than that reported by Aborus et al [17] for two barley varieties (from 479 to 713 mg/100 g).…”
Section: Content Of Total and Individual Phenolics In Fdspcontrasting
confidence: 84%
“…Aborus et al [17] studied the sprouts obtained from two varieties of barley and demonstrated that the vanillic, catechin, epicatechin and gallic acid were the most abundant phenolic acids. Generally, cereals have only small quantities of flavonoids, except barley seeds and sprouts that contain measurable amounts of flavonoids such as catechin, epicatechin [21].…”
Section: Content Of Total and Individual Phenolics In Fdspmentioning
confidence: 99%
“…[41] The TPC of corns germinated at optimum temperatures (35°C) was however comparable with broccoli [39] and oat [41] sprouts. Wheat sprouts of day 7 have TPC level comparable to barley [40] , but lower than sprouts of buckwheat [38] , oat [41] and broccoli. [39] TPCs in wheat and barley grasses were comparable to rice grasses [42] and were higher than all above-mentioned sprouts.…”
Section: Tpc Comparison Between Corn Wheat and Barleymentioning
confidence: 89%
“…Soaking the seeds before sowing may have favored the growth of wheatgrasses because the rate of water adsorption and effect of pre-sowing water treatment on germination potential is higher in wheat than in barley. [10,12,36] TPC in day 10 corn sprouts was higher than in sprouts of lentils [37] and amaranth [38] , comparable to mungbean sprouts [39] , and lower than the sprouts of barley [40] , wheat, and buckwheat. [38] TPC in corn sprouts was about half of sprouts of broccoli [39] and oats.…”
Section: Tpc Comparison Between Corn Wheat and Barleymentioning
confidence: 90%
“…In vitro assessment of the anti-inflammatory activity of QW extract was determined by protein denaturation bioassay, using egg albumin (from fresh hen's egg), according to the method adopted from Aborus et al (15). Absorbances were measured at 660 nm using a vehicle as blank and diclofenac sodium as a drug reference.…”
Section: Reducing Power Assay (Rp)mentioning
confidence: 99%